Policies to Address Banking Sector Weakness : Evolution of Financial Markets and Institutional Indicators - Guerra, Ivan.; Johnston, R. B. (Robert Barry).; Santos, Andre; Youssef, Karim (Washington, D.C. : International Monetary Fund, 2009)
This paper reviews the impact of policies to address banking sector weaknesses through the first months of 2009. At the time of this assessment, central bank intervention had successfully addressed pressures on bank liquidity, but the underlying financial position of financial institutions, particularly the large complex financial institutions (LCFIs), remained precarious. Although Tier 1 ratios had been boosted through the capital injections, tangible common equity (TCE) remained at a critical level for most institutions. Asset quality was weakening, and credit spreads for LCFIs remained wide. Measures had not stemmed the market-driven deleveraging process, and lending surveys pointed to various levels of credit tightening in the United States, Europe, Switzerland, and the United Kingdom. The success of government support measures can be assessed by their impact on bank soundness indicators. Government support measures should have a positive effect on bank soundness by improving bank liquidity, profitability, capital adequacy, and asset quality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Asset; Bank; Commercial Paper; Market; SPN; United States